Digital marketing training for bamboo craftsmen in Sugihmas Village, Magelang Regency - Endah Ratna Arumi; Hasim Febriyanto; Danindra Dien Diatriansyah Yunesta; Muhammad Iqbal Al Ghozali; Wakhidatun Fauziah; Sonia Ajie Wulandari (Community Empowerment, 2022)
Optimizing products and added value through empowerment and digital marketing in Gatak Hamlet intends to educate bamboo craftsmen in Gatak Hamlet, Sugihmas Village, on how to use social media to sell their products. The craftsmen were provided materials as well as instruction on how to use social media to advertise their handicraft products. The Kemmis methodology was adopted, which starts with the planning, implementation, and reflection stages. As a result of this program, bamboo craftsmen in Gatak Hamlet, Sugihmas Village have gained a better grasp of online product marketing via social media, as well as steps and tips for marketing items via social media.